Accounting, accountability and crisis management : lessons from Italy's pandemic response - Costa, Ericka; Contrafatto, Massimo; Parker, Lee D. (Routledge, 2025)
"Conventional economic and accounting systems have been exposed by the limitations of market-driven mechanisms, where public services, education and healthcare have been subordinated to profit, exacerbating the inequalities between people and countries. Italy was one of the earliest countries to be affected by the COVID-19 pandemic and also one of the hardest-hit. The successes and failures of the Italian response provides a blueprint for the factors determining the ability of institutions to meet these challenges. This book presents a multifaceted analysis and reflection of the challenges that various types of organisations - public, private and non-profit - have had to face during the pandemic. It contributes to the creation of robust strategies for institutions worldwide to be able to respond promptly and equitably to future emergencies and offers insights for developing policy and practice, with respect to global leaders' accountability for and management of exceptional events. It addresses three main subjects: extraordinary events and their challenges for business and organisations; the nature and roles of interdisciplinary accounting and accountability in a pandemic environment; and how the global pandemic is impacting accounting and accountability in diverse contexts, such as public services, healthcare, education, and NGOs. With a focus on institutional approaches to establishing, maintaining and discharging accountability throughout the pandemic, the insights of this book are invaluable to both students and practitioners seeking to bolster institutional resilience in an increasingly uncertain world. Both management and accounting communities can learn from this extraordinary global event to promote the process of transforming how business and societies operate"-- Provided by publisher.
Keywords: Accounting -- Italy.; Crisis management -- Italy.; Organizational resilience -- Italy.; COVID-19 Pandemic, 2020- -- Economic aspects -- Italy.; elektronické knihy; electronic books